The Effect of Digital Marketing on Purchase Decisions Among Youth In Sarawak - Jessie Paige, Roger; Asmaul Husna, Haris Fadzilah (2023)
The objective of this study is to identify the relationship between email marketing, online advertising, social media marketing and mobile marketing on the purchasing decision I fashion industry among youths in Kuching, Sarawak. This study focuses on four digital marketing channels such as e-mail marketing, online advertising, social media marketing and mobile marketing which can lead to the purchase decisions of youths in Kuching, Sarawak. The sampling method used is the convenience sampling method. There are 374 respondents involved which are of undergraduate students of University of Malaysia, Sarawak. The data is analyzed by using Statistical Package for the Social Sciences (SPSS), Pearson Correlation Coefficient and Multiple Linear Regression analysis. From the findings, it is expected that there are positive and significant relationships between email marketing, online advertising, social media marketing and mobile marketing with purchase decisions of fashion brands among youths. This study contributes to bringing awareness to fashion brand business owners on the effectiveness of utilizing digital platforms in their business and the digital platforms that have the most impact on youth purchasing.